2014
DOI: 10.3906/vet-1405-6
|View full text |Cite
|
Sign up to set email alerts
|

The avian ovary and follicle development: some comparative and practical insights

Abstract: This review focuses on recent research related to the avian ovary and, in particular, cellular mechanisms mediating embryonic growth of the ovary, postembryonic follicular development, and the process of follicular selection. Attention is drawn to a variety of fundamental, yet unresolved, aspects of ovarian function, several of which are uniquely related to avian reproductive strategies. Some notable differences in ovarian function between birds and the most closely related extant group, the crocodilians, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 62 publications
3
51
0
1
Order By: Relevance
“…The testes develop due to gene dosing with increased expression of the Z-linked transcription factor gene, doublesex and mab-3-related transcription factor 1 (DMRT1). 6,7 Anti-M€ ullerian hormone (AMH) is synthesized and secreted by the embryonic testis with greater expression in the embryonic testes than the ovaries. 8e10 AMH directs the regression of the paired M€ ullerian ducts.…”
Section: Embryonic Development Of the Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The testes develop due to gene dosing with increased expression of the Z-linked transcription factor gene, doublesex and mab-3-related transcription factor 1 (DMRT1). 6,7 Anti-M€ ullerian hormone (AMH) is synthesized and secreted by the embryonic testis with greater expression in the embryonic testes than the ovaries. 8e10 AMH directs the regression of the paired M€ ullerian ducts.…”
Section: Embryonic Development Of the Reproductive Systemmentioning
confidence: 99%
“…11 The avian oviduct is derived from the embryonic M€ ullerian duct; the former term encompassing the entire reproductive tract from infundibulum to the cloaca. 7 Regression of the right oviduct is induced by AMH. 10 Parenthetically, AMH also plays an important role in development of tubules in the testes.…”
Section: Embryonic Development Of the Reproductive Systemmentioning
confidence: 99%
“…A few signaling pathways have been implicated in the process of follicle recruitment in domestic laying hens [1,[5][6][7]; however, the exact underlying molecular mechanisms are still unclear. It has been reported that surrounding somatic cells have a well-coordinated interplay with the oocytes, and this interaction is believed to promote the process of follicle recruitment from the available pool [3].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, this process seems to be complex and highly coordinated, involving a number of divergent biological effects on the maturation of oocytes and differentiation and proliferation of granulosa and theca cells within the ovarian follicles [8]. In addition, the follicle-stimulating hormone (FSH) has been implicated in facilitating the recruitment of follicles [6,7,[9][10][11][12]. Similarly, follicle stimulating hormone receptors (FSHR) are reportedly expressed on the granulosa layer of developing follicles, and mRNA expression of these receptors (FSHR) changes with progressing follicular maturation [3,6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Small follicles also produce a significant amount of ovarian oestrogens [Armstrong, 1984]. Cells expressing the enzyme aromatase, which synthesise oestrogen from androgen precursors, are localised to the theca externa of larger follicles, whereas pregnenolone, progesterone, and androgen precursors are almost exclusively produced by the theca interna [Johnson, 1986[Johnson, , 2014. On the other hand, the granulosa cells of the growing previtellogenic and vitellogenic follicles synthesise progesterone de novo, i.e., from cholesterol and pregnenolone.…”
Section: Introductionmentioning
confidence: 99%